Application of non-linear programming to optimize buildings' solar exposure. (May 2017) - Fokaides, P.A.; Panayidou, A.; Hadjichristos, C.; Phocas, M.C.
Abstract: Buildings' passive solar energy utilization is based on the absorption of solar radiation by the building interior, as solar radiation penetrates through the glazed elements, or by the building shell per se. The quantity of absorbed solar energy depends on building's shape, the orientation of its exposed surfaces to radiation, the shading equipment and the absorption coefficient of the concerned surfaces. This study introduces a novel approach that enables the optimal design of a building shell based on the optimization of its solar exposure. Non-linear programming (simplex algorithm) was used for determining the optimal building geometry. The objective function considered was related to the optimization of building's solar heat gain. The optimization constraints represented a list of morphological and seasonal restrictions expressed as non-linear functions. The cumulative seasonal and annual solar exposure of the considered building was resolved by employing the methodology described in the EN ISO 13790:2008 standard. The investigated subject was a single story, convex quadrilateral detached dwelling with one pair of parallel sides. The calculations were performed for two typical meteorological years (TMY) of two European cities, each one representing dense populated latitudes of the European continent, with summer and winter dominant weather conditions. The results of this study are expected to contribute to the establishment of a parametric design procedure aiming to the optimization of building's annual and seasonal solar exposure, based on specific design inputs. Highlights: Conceptual study of a novel technique for building envelope environmental design. Non-linear programming to optimize solar exposure under diverse weather conditions. Diverse solar radiation levels didn't affect the optimal building geometry. Fenestration thermal properties have significant impact on the optimal geometry.